2017
DOI: 10.3126/jpn.v7i1.16945
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological pattern of testicular lesion

Abstract: Background: Testicular tumors are rare type of tumors affecting adolescents and young adults. The testicular tumors constitute 4th most common cause of death from neoplasm in a younger male.The present study is undertaken to analyze the pattern and age wise distribution of testicular lesions in our hospital. Materials and Methods:This was a prospective study done over a period of 4 years from November 2012 to October 2016, after taking approval of the ethics committee and informed consent from the patients. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
1
Order By: Relevance
“…Unlike the present study, the most common age group, according to Dhawale et al [6], Sharma et al [3], and Baidya et al (2017) [7], was found to be 11-20 years (second decade). Most of the non-neoplastic lesions in this study contributed to the highest number of cases in the sixth decade.…”
Section: Discussioncontrasting
confidence: 83%
“…Unlike the present study, the most common age group, according to Dhawale et al [6], Sharma et al [3], and Baidya et al (2017) [7], was found to be 11-20 years (second decade). Most of the non-neoplastic lesions in this study contributed to the highest number of cases in the sixth decade.…”
Section: Discussioncontrasting
confidence: 83%
“…Torsion testis was also the commonest non-neoplastic pathology in other studies. [6,7] Time is the most critical factor in the emergency care of torsion testis .The success of surgery within 4-8 h from the onset of the symptoms is around 90%-100%, but after 12 hours it is 50% and after 1 day only 10% . [8] Delay can be fatal and may lead to impaired fertility and loss of the testicles.…”
Section: Torsion Testismentioning
confidence: 99%
“…[11] In separate studies, Reddy et al reported 86%, while Patel et al and Baidya et al each registered 85% as nonneoplastic. [121314] The above conclusions were different from Robertson's registered 31.5 versus 68.5%. [15] Earlier studies firmly established diversity of neoplastic lesions across the regions of the world and rareness of testicular tumors in our populace.…”
Section: Discussionmentioning
confidence: 75%
“…[1113] A 2-year comparison in Nepal also recorded torsion as the most common. [14] The variations may be due to variances in genetic blueprints and exposure to environmental elements that included chemical integrals, radiations, and infective agents.…”
Section: Discussionmentioning
confidence: 99%